(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Improving the socio-economic situation of women in our country, increasing their entrepreneurial activity, providing vocational training and employment, further enhancing the role of businesswomen in economic development. Human capital, human rights, gender equality and sustainable development are a chain of interrelated issues that are relevant today. Gender equality is important in itself, it manifests itself in the role of women in the development of society and the strong influence of human potential on labor productivity. This article will analyze issues related to the improvement of the women’s labor market, the continuation of the policy of increasing the socio-economic activity of women, on the basis of these analyses, conclusions and proposals will be formulated.